ANALISIS LEVERAGE DAN AKTIVITAS DALAM MENGENDALIKAN PROFITABILITAS PADA PT ASTRA OTOPARTS, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Deby Rizki Amanda Lubis; Jubi Jubi; Ady Inrawan; Ernest Grace (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2019)
The purpose of this research to know: 1.  The description of leverage, activity and profitability at PT Astra Otoparts, Tbk which are listed on the Indonesia Stock Exchange. 2. What factors are cause profitability at PT Astra Otoparts, Tbk which are listed on the Indonesia Stock Exchange tend to decline.   This research was conducted using Qualitative Descriptive Analysis and Inductive Analysis. This research was conducted based on secondary data from company financial statements obtained from the Indonesia Stock Exchange.        The results of the study can be concluded that: 1. Leverage as measured by Debt to Assets Ratio (DAR) fluctuates and tends to increase. 2. Activities measured by Working Capital Turnover (WCT) fluctuate and tend to increase. 3. Profitability as measured by fluctuating Return On Assets (ROA) tends to decrease. 4. Factors that cause decreased profitability are increased business debt, increased inventory and increased cost of goods sold so that the resulting profit decreases.            The results of the study suggest: 1. It is best if the company needs to review the use of corporate debt in financing its activities by carrying out control of accounts receivable and strict supervision and evaluation periodically, so that the risk of such debts can be minimized. 2. It is better for the company to pay more attention to the management of supplies effectively and efficiently so as to produce increased sales. Effective inventory management also needs to pay attention to inventory storage so as not to overload, both obsolete inventory and unsold inventory. 3. It is better for the company to pay more attention to using its assets to generate high sales accompanied by an increase in profit after tax owned by the company to produce good profits. On the other hand the company must also consider the level of operating expenses so as not to over-pressure profits. Keywords: Leverage, Activity, and Profitability